1996
DOI: 10.1111/j.1532-5415.1996.tb01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Good Nutritional Oral Intake Is Associated with Equal Survival in Demented and Nondemented Very Old Patients

Abstract: Dementia developing in very old age is not necessarily associated with malnutrition and decreased life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 28 publications
1
31
1
Order By: Relevance
“…In this population, neoplasias were the main determinants of mortality, particularly in the women, whereas the neurodegenerative diseases had a controversial protective effect because dementia is considered a strong predictor of mortality in the elderly (Guehne et al 2005), also regardless of APOE genotype (Little et al 2009). Although, a study reported that dementia developing in very old age is not necessarily associated with decreased life expectancy (Franzoni et al 1996), in our study population, the low mortality risk for this condition could be due to the short time of the follow-up. Further studies are needed to clarify the role of APOE variants on mortality in elderly patients independently of age-related diseases.…”
Section: Discussioncontrasting
confidence: 65%
“…In this population, neoplasias were the main determinants of mortality, particularly in the women, whereas the neurodegenerative diseases had a controversial protective effect because dementia is considered a strong predictor of mortality in the elderly (Guehne et al 2005), also regardless of APOE genotype (Little et al 2009). Although, a study reported that dementia developing in very old age is not necessarily associated with decreased life expectancy (Franzoni et al 1996), in our study population, the low mortality risk for this condition could be due to the short time of the follow-up. Further studies are needed to clarify the role of APOE variants on mortality in elderly patients independently of age-related diseases.…”
Section: Discussioncontrasting
confidence: 65%
“…This is supported by other studies on family style mealtimes (Franzoni, Frisoni, Boffelli, Rozzini, & Trabucchi, 1996;Nijs et al, 2006). Thus, sharing meals can probably be considered simply as a good practice issue more than a therapeutic issue.…”
Section: Resultsmentioning
confidence: 63%
“…Our study relates body mass index to brain atrophy in persons who are relatively early in the course of their cognitive decline. These results would not apply to persons in very advanced states in dementia, for whom lack of adequate food intake is often a major predictor of mortality (Franzoni et al, 1996). Rather, our work is best applied from the standpoint of understanding how control of body weight and other lifestyle factors may promote healthy brain aging and reduce the partly preventable risks for cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 99%